Youth employment: A key to future human development of Bangladesh - Matin, Imran (UPL, 2024)
This book chapter was published in the book named National Human Development Report 2021 and the definite version is available at : https://erd.portal.gov.bd/sites/default/files/files/erd.portal.gov.bd/page/83abb6f9_b264_45f9_92c0_2596b2421dc9/National_Human_Development%20(1).pdf